Key Success Factors of Renewable Energy Projects Implementation in Rural Areas of Indonesia - Wati Hermawati; Ishelina Rosaira (STI Policy and Management Journal, 2017)
This paper is an exploratory study on renewable energy implementation in the rural areas of Indonesia. The study aim was to investigate the factors contributing to the sustainability of renewable energy projects in the rural areas. It mostly uses a qualitative approach. Primary data was mainly obtained from in-depth interviews conducted in site areas with the project owners, project managers, a key person in each local government, industry representatives, and the local community, including local leaders and users of renewable energy. Secondary data in the form of various official project reports was also used. The results indicated that the success of energy project implementation lay not only in good technology performance and long-term maintenance, but was also highly dependent on six key factors, namely: (1) project planning and development; (2) community participation; (3) active communication and beneficiaries; (4) availability of maintenance program, workshop and technician; (5) project management and institutionalization; (6) local government support and networks. The findings from this study provide useful insights to all stakeholders involved in the implementation of renewable energy technology for the rural areas in Indonesia.